Enhancing Students’ Voice from A Meaningful Presentation - Pratama, Ridar Kurnia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
The new curriculum adds presenting as one of the skills in language subjects including English. The practice aimed to find out the effectiveness of presenting skill in enhancing students’ voice to communicate. The practice applied qualitative design by using a problem-based approach. The focus groups of participants were 8th grader students in Brighton Junior High School, Depok. Problem-based approach helped students to figure out the topic that found their interest and helped them to figure out the important topics to be presented to their teacher. The topics that were found by students not only presented as a description but as a suggestion, critics and an offering to be applied at school. Therefore, a meaningful presentation is a further way for students to express their idea in a good way, so that teachers could show their care towards students’ voice. Problem-based approach could be the best way to let students explore their surroundings and build their empathy. Furthermore, the topics that they have found can be facilitated by the teacher to be presented to the school leaders as their consideration to apply it.